AMERICAN JEWS AS A WHITE ETHNIC AND HOW THEY WERE PERCEIVED: A SOCIOLOGICAL APPROACH - Rizqy A.R. Ahmad; Muh Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2020)
This study aims to determine the changes of American Jews social status from the ‘other’ to the white ethnic. Social Identity theory is used in order to breakdown how the American Jews were perceived. The classification as a white ethnic, while it has its benefits, does not automatically put the American Jews and the WASP in the exact same position. Rather, the American Jews managed to stay within their ethnic boundaries while enjoying the white privilege.